2019
DOI: 10.1136/bmjgast-2019-000330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gastric and duodenal biopsy results in patients presenting with dyspepsia: a cross-sectional study in a middle eastern population

Abstract: ObjectiveCorrea’s cascade is a ‘Model for Gastric Cancer Development’ described by Peleyo Correa. The reversibility of Correa’s cascade remains debatable. The literature contains insufficient data on the specific stage of the cascade during which Helicobacter pylori is detected, treated, and the effect on prognosis. Herein, we aim to determine the prevalence of various precancerous and cancerous gastric lesions in patients presenting with dyspepsia, the prevalence of gastritis and H. pylori infection, the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Ghosn et al, conducted a study of 1428 patients presenting with dyspepsia who underwent gastroscopy with gastric and duodenal biopsies. 14 The authors found that age above 40 years was associated with increased likelihood of exhibiting abnormal gastric biopsy result. Gastritis and metaplasia were detected more frequently than glandular atrophy (P<0.001) with gastritis being present the most (P<0.001).…”
Section: Resultsmentioning
confidence: 98%
“…Ghosn et al, conducted a study of 1428 patients presenting with dyspepsia who underwent gastroscopy with gastric and duodenal biopsies. 14 The authors found that age above 40 years was associated with increased likelihood of exhibiting abnormal gastric biopsy result. Gastritis and metaplasia were detected more frequently than glandular atrophy (P<0.001) with gastritis being present the most (P<0.001).…”
Section: Resultsmentioning
confidence: 98%
“…In Lebanon, many factors have been found to be associated with increased risk of stomach cancer including a high sodium diet, obesity, smoking, and moderate alcohol consumption [9]. However, to the best of our knowledge, epidemiological data of PGL in the Lebanese population has never been reported.…”
Section: Introductionmentioning
confidence: 91%
“…Histopathological study helps in confirmation of a benign/inflammatory or malignant condition, allowing for an early management without unnecessary delay. Endoscopy is known to be less discomforting, and well tolerated, with a direct visual of lesion [2,4,7].…”
Section: Chronic Gastritis 13mentioning
confidence: 99%
“…Clinical symptoms vary from dysphagia to dyspepsia to altered bowel movements, which pathologically could vary between the common non-neoplastic and neoplastic lesions. Dyspeptic symptoms, secondary to H.pylori infection can lead to debilitating consequences, particularly increasing the risk of adenocarcinoma [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%